Memory Efficient Loss Recovery for Hardware-based Transport in Datacenter - Lu, Yuanwei; Chen, Guo; Ruan, Zhenyuan; Xiao, Wencong; Li, Bojie; Zhang, Jiansong; Xiong, Yongqiang; Cheng, Peng; Chen, Enhong (ACM APNet, 2017)
Limited by the small on-chip memory, hardware-based transport typically implements go-back-N loss recovery mechanism, which costs very few memory but is well-known to perform inferior even under small packet loss ratio. We present MELO, an efficient selective retransmission mechanism for hardware-based transport, which consumes only a constant small memory regardless of the number of concurrent connections. Specifically, MELO employs an architectural separation between data and meta data storage and uses a shared bits pool allocation mechanism to reduce meta data on-chip memory footprint. By only adding in average 23B extra on-chip states for each connection, MELO achieves up to 14.02 x throughput while reduces 99% tail FCT by 3.11 x compared with go-back-N under certain loss ratio.